An Observational Study on Autopsies - Uzma Zaheen, Khyzer Hayat Sukhera, Muhammad Hassaan, Mansoora Mirza, Tayyaba Amjad Mustafa, Shaiqa Ramzan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find out and evaluate to the number of cases, natural of cases (known, unknown) and unique reference to mode, manner and cause of death of medicolegal autopsies Study Design: Cross-sectional study. Place and Duration of Study: Department of Forensic Medicine, Lahore General Hospital, Lahore from 1st January 2021 to 31st December 2022. Methodology: Two hundred and forty six medicolegal autopsies were gathered. The perceptions kept in proforma with an accentuation on the gender of subjects, cause of death (natural, un-natural), manner of death, mode of death of known and unknown cases and month-wise variation of post-mortems. Results: One hundred and eight were natural deaths and 138 were un-natural. Gunshots represented 36% of the deaths through 18% were physical assault related deaths.158 cases were known while the 88 were obscure cases. Conclusion: In larger part of the medicolegal post-mortems male populace was involved and brought about by gunshot wounds (homicidal). August and October were the months where greater part of the cases came. Keywords: Medicolegal autopsy. Mode, Manner, Known and un-known